1955
DOI: 10.1149/1.2430056
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Titanium by Fluoride Electrolysis

Abstract: Preparation of commercially pure titanium metal powder by electrolysis of K:~TiF~ in molten NaCI is described. The process is carried out under an inert atmosphere in an all-graphite cell. Operating conditions of the electrolysis and their effect upon the metal so produced are discussed. Preparation of the K2TiF~ and the electrolytic procedure are completely described. The process is capable of producing metal of high purity which may be consolidated and fabricated by standard techniques as applied to metal po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1955
1955
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Previous reports have shown that metallic titanium can be electrodeposited only from high-temperature molten salts as electrolytes. Generally, chlorides, [1][2][3][4][5][6][7][8][9][10][11][12][13] fluorides, [14][15][16][17][18] and chloride-fluoride mixtures [19][20][21][22][23][24][25][26][27][28][29][30][31] have been used as the molten salt electrolytes for titanium electrodeposition. The morphology of the Ti deposits closely depends on the type of salts used as electrolyte.…”
mentioning
confidence: 99%
“…Previous reports have shown that metallic titanium can be electrodeposited only from high-temperature molten salts as electrolytes. Generally, chlorides, [1][2][3][4][5][6][7][8][9][10][11][12][13] fluorides, [14][15][16][17][18] and chloride-fluoride mixtures [19][20][21][22][23][24][25][26][27][28][29][30][31] have been used as the molten salt electrolytes for titanium electrodeposition. The morphology of the Ti deposits closely depends on the type of salts used as electrolyte.…”
mentioning
confidence: 99%
“…The solution was passed through a hot filter and cooled. The resulting potassium hexafluorotitanate crystals were dried in a vacuum, first at 363 K for 24 h and then at 423 K for 6 h. 26 Barium chloride (chemical pure) was dried in a vacuum oven at 433 K for 24 h. Barium fluoride (analytically pure grade), magnesium fluoride (high purity) and calcium chloride (pure grade) were used without additional processing.…”
Section: Methodsmentioning
confidence: 99%
“…The solution was passed through a hot filter and was evaporated. The resulting K 2 TiF 6 crystals were dried in a vacuum, first at 363 K for 24 h and then at 423 K for 6 h. 35 Calcium chloride (Sigma Aldrich 99.0% min.) was dehydrated in vacuum at 413 K for 2 h. 36 The (NaCl-KCl) equimol -NaF (10 wt%) electrolyte was placed into a glassy carbon crucible, loaded into a retort of the electrochemical cell, the above-described vacuum-melting operations were repeated, then K 2 TiF 6 and CaCl 2 were introduced into the melt.…”
Section: Methodsmentioning
confidence: 99%